The Impact of the COVID-19 Pandemic on Examination of Pregnant Women (Antenatal Care): A Literature Review - Siti Roudhotul Jannah; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2022)
COVID-19 pandemic is making universal, radical, and very rapid changes in the health services of many countries around the world, especially obstetrics. The World Health Organization states that Coronavirus Disease 2019 (Covid-19) is a global pandemic. As one of the vulnerable groups, pregnant women need to avoid Covid-19 transmission and maintain their health in the pandemic period. The purpose of the study was to look at some of the research together and gain a frame of mind in solving problems about antenatal care in the time of the covid-19 pandemic. Research methods using literature review studies are obtained through the database of international journal providers Proquest and Jurnal Scientific Indonesia through google scholar with keywords according to MESH (Medical Subject Heading) namely "Pandemic Covid-19", "Antenatal Care". As a result of 12 studies, 8 showed negative ratings in which respondents did not make antenatal care visits citing fear of being infected with the virus, felt antenatal care was inadequate and caused great emotional damage to users. 2 of the 8 articles have also implemented online-based health care methods, using smartphone apps specifically designed to be used as a medium for sending health messages so that pregnant women can monitor the health of their pregnancies. As well as reducing direct interaction during the Covid-19 pandemic without compromising pregnancy outcomes. So that optimal education is needed from health workers, to increase the awareness of respondents in determining good behavior during pregnancy in order to undergo pregnancy and childbirth well.